2013
DOI: 10.1111/bjh.12609
|View full text |Cite
|
Sign up to set email alerts
|

Romiplostim in children with chronic immune thrombocytopenia (ITP): the French Experience

Abstract: SummaryA minority of children with chronic immune thrombocytopenia (ITP) require therapeutic intervention to prevent haemorrhagic risk. This retrospective national study evaluated romiplostim in childhood non‐responsive or refractory chronic ITP. Between 2009 and 2012, 10 patients whose Buchanan score was 3–4 were treated with romiplostim. The median duration of thrombocytopenia was 1·9 years (0·8–15). The median duration of romiplostim treatment was 9 months (3–36). A response was observed in 5/10 patients (o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 15 publications
0
27
0
1
Order By: Relevance
“…In the last few years, romiplostim and eltrombopag have been increasingly used in some haematological disorders. Reports of sustained remission after thrombopoietin receptor agonist discontinuation in adults (Červinek et al , ) and children (Kühne, ) suffering from ITP have been reported, and encouraging results have been published in some ES children, (Pasquet et al , ; Seidel et al , ). Its use in ES remains anecdotal, however, and might be clarified by future studies.…”
Section: Second and Further‐line Treatmentmentioning
confidence: 99%
“…In the last few years, romiplostim and eltrombopag have been increasingly used in some haematological disorders. Reports of sustained remission after thrombopoietin receptor agonist discontinuation in adults (Červinek et al , ) and children (Kühne, ) suffering from ITP have been reported, and encouraging results have been published in some ES children, (Pasquet et al , ; Seidel et al , ). Its use in ES remains anecdotal, however, and might be clarified by future studies.…”
Section: Second and Further‐line Treatmentmentioning
confidence: 99%
“…In the open‐label phase of these trials, 80% of patients were able to achieve a platelet count ≥50 × 10 9 /l at least once . Additional data about the use of these agents in pediatric ITP is limited to small single center retrospective reviews and case series focused on children with persistent and chronic ITP …”
Section: Introductionmentioning
confidence: 99%
“…[6,7] Additional data about the use of these agents in pediatric ITP is limited to small single center retrospective reviews and case series focused on children with persistent and chronic ITP. [9][10][11] Despite a paucity of literature regarding TPO-RA use in children, physicians are prescribing TPO-RAs to pediatric patients off-label and outside of clinical trials. Furthermore, physicians may not be reserving these agents exclusively for chronic primary ITP, the only group in whom these agents have been investigated and are indicated.…”
Section: Introductionmentioning
confidence: 99%
“…39 All children had a bone marrow aspiration at diagnosis, which was compatible with ITP. The children were treated for 3-36 months with a romiplostim dose between 4-10 mg/kg, starting at 1 mg/kg with weekly escalation to a maximum of 10 mg/kg.…”
Section: Experience Of Tpo-ras In Pediatricsmentioning
confidence: 99%